М’ясомісткі продукти з буряковим барвником - Пасічний, Василь Миколайович; Тимошенко (Кремешна), Ірина Володимирівна; Дубковецький, Ігор Володимирович (My University, 2014)
В роботі наведено результати експериментальних досліджень стабілізації натурального пігменту бурякового соку з метою отримання натурального червоного барвника, досліджено можливість отримання сухого бурякового барвника у вигляді комплексної суміші з подальшим її використанням у виробництві м’ясомістких продуктів, які потребують додаткового підфарбовування не м’ясної сировини, доведена можливість використання комплексної суміші з барвником в якості харчової добавки для покращення структурних та органолептичних властивостей. In the presented work the attention is paid to the problem of removal, selection and production management of the red natural food colour, received on the basis of natural pigments of table beet for application in meat and meat containing products. It has been proved that it is possible to stabilize beetroot juice with mixture of food acid and salt for increasing of thermal resistance of pigments with the subsequent use in minced meat systems, active acidity of which approximates to neutral. Derivation of dry beetroot colourant in the form of complex mixture with rice flour enables to apply it as a food additive for improvement of structural and colour-forming properties for meat-containing boiled sausages that require additional colouring of non-meat products. The optimal degree of hydration of rice flour and beetroot colour mixture, duration and temperature of drying, their influence on the mixture technological parameters have been determined. A convection method combined with infrared radiation was used for drying, that allows to reduce the amount of energy consumption. It has been determined that the colourant in the form of a coloured powder has a better colouring property compared to liquid stabilized juice. This is caused by better stability of betanin in the dry form.
Keywords: м’ясомісткі продукти; буряковий сік; стабілізація; натуральний барвник; комплексна суміш; meat-containing products; beet juice; stabilization; natural dye; кафедра процесів і апаратів харчових виробництв; кафедра технології м’яса і м’ясних продуктів